Historiographical Narratives and Demonological Representations. The Devil in the Cloisters of Viceregal Peru. 17th century (Pontificia Universidad Católica de Chile. Dpartamento de Humanidades, 2011)
In seventeenth century Peru, which was characterized by an intense religiosity, virtuous men and women lived in a permanent confrontation with the devil that was understood as an expression of the conflict between Good and Evil that existed from the beginning of time and would last until the end of time. The devil, attempting the perdition of the "saints", tried to destroy the work of God, because they were his chosen. But, on the other hand, the devil acted in these matters with Gods permission who in this way tried to test the strength of his favored children. Using hagiographic accounts, this article analyzes these phenomena and describes the strategies that the devil used in order to make the "saints" fall. It also examines the means those turned to in their struggles and the meaning that those confrontations had. The article tries to understand why for seventeenth-century Peruvian society, and more so for the "saints", the devil maintained a prominence in daily life throughout the century, while in Europe its image tended to become diluted.